Hygrothermal Effect on Mechanical and Thermal Properties of Filament Wound Hybrid Composite - Osman, Edynoor; Abd Rashid , Mohd Warikh; Abd Manaf, Mohd Edeerozey; Mohamad, Effendi; Salleh, Mohd Rizal; Ito, Teruaki; Moriga, Toshihiro (Penerbit UTeM, 2016)
This study focused on the hygrothermal effect on filament wound glass-carbon/epoxy hybrid composite. Non-geodesic pattern of filament winding with a winding speed of 15.24–30.48 lm/min was used. Fiber tensioning weight of one kg and a winding angle of 30° were created to produce wound samples of the hybrid composite. The hybrid composite was wound by using a ±30° orientation with a total of six layers. Hygrothermal effect was conducted in a humidity chamber for three days (72 h). Control temperatures of 60 and 80°C were established, and humidity percentages of 50%, 70%, and 90% were used. Moisture absorption test showed that heat and humidity in most of the hybrid samples gradually increased. As a result, glass-carbon 80°C/90% showed the highest absorbed moisture at 0.77%. The involvement of highest heat and humidity showed the decline in the values of tensile and flexure strengths at 75.80 and 157.15 MPa, respectively. Fractography analysis using Stereo Microscope Stemi 2000-C indicated that glasscarbon/ epoxy 80°C/90% showed catastrophic damage, large crack, and longest delamination of fiber pullout at 10.39 mm. The fracture criterion revealed that the involvement of heat and humidity significantly affected the mechanical and physical properties of hybrid composite material.